الدور الوسيط للشمول المالي في العلاقة بين نظم المعلومات المحاسبية والميزة التنافسية (دراسة ميدانية على عينة من المصارف الحكومية بولايات السودان المختلفة). - محمد الناير محمد; عمر ابكر اسحاق اد محمد حسن آدم ازر&#1602 (Arab Journal for Humanities & Social Sciences, 2025)
The study aimed to identify the mediating role of financial inclusion in the relationship between accounting information systems and competitive advantage in Sudanese government banks in the various states of Sudan and to achieve the objectives of the study, the study model and hypotheses were built depending on the study literature, and the use of previous studies in the development of the study scale, and a questionnaire was designed to collect primary data, where (400) questionnaires were distributed and (247) valid forms were recovered for analysis and to ensure the degree of reliability in the data, the Alfakronbach test was used. The path analysis program relied on the social sciences program (SSPSS) in order to find the model that fits well for the data collected enough to be a representation of reality and the interpretation of the data as such. The study reached a set of results, the most important of which are the following: There is a significant impact relationship between accounting information systems and competitive advantage, and there is a significant impact relationship between accounting information systems and financial inclusion, and there is a significant impact relationship between financial inclusion and competitive advantage. The study also found that there is no effect of financial inclusion as an intermediate variable between accounting information systems and competitive advantage.